Cambrian (Stage 4 to Wuliuan) brachiopods from Sonora, Mexico. (November 2022) - Holmer, Lars E.; Clausen, Sébastien; Popov, Leonid E.; Ghobadi Pour, Mansoureh; Liang, Yue; Zhang, Zhifei; Palafox Reyes, Juan José; Sosa-Leon, Jesùs Porfirio; Buitrón-Sánchez, Blanca Estela
Abstract: The Cambrian successions at the Chihuarruita Hill outcrop, Sonora, Mexico, have yielded two successive linguliform brachiopod assemblages that are transitional between Cambrian Stage 4 and the newly recognized global Wuliuan Stage. The lowermost assemblage includes Dictyonina sp., Paterina sp., Eothele sp., Hadrotreta rara ? (Cooper), and Linnarssonia arellanoi ? (Cooper), coming from the upper part of the Buelna Formation. The younger, recently named El Gavilán Formation contains a more diverse linguliform brachiopod assemblage, including Acrothele concava Cooper, Batenevotreta ? mexicana n. sp., Dictyonina minutipuncta Cooper, Eothele sp., Eoobolus sp., Hadrotreta rara ? (Cooper), Linnarssonia arellanoi ? (Cooper), Micromitra sp., Paterina sp., and Prototreta sp. The El Gavilán Formation contains a diverse trilobite fauna suggesting Delamaran age in terms of the Laurentian regional stratigraphical scheme. The base of the global Wuliuan Stage and Miaolingian Series is defined by the first occurrence of Oryctocephalus indicus ; in the absence of the index species, the base should be provisionally placed at the base of the El Gavilán Formation. The Wuliuan age of the brachiopod assemblage recovered from the El Gavilán Formation is supported by the occurrence of Acrothele in the Cambrian biostratigraphical succession of Himalaya, where the genus makes its first appearance in the Kaotaia prachina Zone. In addition, the co-occurrences of Acrothele and Eothele can be taken as an indication of the Wuliuan age of the fauna. A new biogeographic analysis confirms that the Eothele Fauna first appeared at the end of Cambrian Stage 4, as a result of increased faunal migration within the southern tropical latitudes directed from Australasian Gondwana to Laurentia. UUID: http://zoobank.org/6598f51f-cb07-4df3-bd1f-025a13e64edf